Surface curing effect on reflection response of hardened cementitious mortar samples. (November 2021) - Hasar, Ugur Cem; Izginli, Mucahit; Ozturk, Hamdullah; Korkmaz, Huseyin; Cevik, Abdulkadir; Irshidat, Mohammad Refaat
Abstract: Surface curing effect of hardened engineering cementitious mortar (ECM) samples with distinct water-to-binder ratios ( w / b ) is analyzed by recording amplitude of reflection response | Γ | or conductance term g measured by a microwave open-ended waveguide probe. Frequency dependencies (between 3.95–5.85 GHz) of | Γ | and g measured from various surfaces (top, bottom, and lateral) of ECM samples with w / b = 0 . 2 and 0.3 are presented at the 720th days of curing (hardened ECM). In addition, their temporal dependencies (over 1–9 and 720–815 days) are presented for the frequency value of 4.56 GHz. From our analysis, contrary to top and lateral surface behaviors, it is noted that crossover between g values measured from bottom surfaces of ECM samples with w / b = 0 . 2 and 0.3 delays for a long time (around 550 days). Propagation-related studies should take into account reflection profiles varying with wall height for accurate prediction. Highlights: Surface curing effect of hardened engineering cementitious mortars (ECMs) are analyzed. Temporal reflection values (over 1–9 and 720–815 days) are presented at 4.56 GHz. Crossover between reflection from bottom surfaces of ECMs delays to around 550 days. Reflection profiles varying with wall height should be used for accurate modeling.